Relação entre as Características Morfológicas e a Qualidade da Cortiça - Pestana, Miguel; Carneiro, Luís; Lousada, José; Sardinha, Raúl (Silva Lusitana, 2011)
. The main drive of this study was to contribute for a better knowledge about the relationship between the quality of cork and its morphology, aiming to finding out the predictive capacity of the morphological characteristics and their weight to discriminate and select cork quality. Board cork samples were taken out from 9 sample trees (3 trees x 3 sites) and they were prepared to allow quantitative classification according to punctuation classification as described by CARVALHO (1992). Data analysis was done using numerical taxonomy methods. Results generated allow emphasizing that: • The use of punctuation criteria showed the usefulness and significance of some morphological characteristics to segregate cork quality; • Good quality corks were characterized by higher values of the belly's color and low values of the belly’s relief, and its unevenness, and the size and density of the inclusions in the cork mass as well; • Bad quality corks showed a set of dominant morphological characteristics: density, distribution, aggregation and size variation of lenticels and a pronounced relief and also the size of incrustations on the belly; • The introduction of one more parameters – apparent density (DA) – in the morphological analysis did not alter quality classification
Keywords: Cork; morphology; multivariate analyses; Quality

Relationships of Selected Soil Parameters and Natural Pastures Yield in the Montado Ecosystem of the Mediterranean Area Using Multivariate Analysis - Ferreira, Eugénio Mendes; Simões, Nuno; Castro, Isabel Videira e; Carneiro, Luís (Silva Lusitana, 2010)
Chemical, physical and biological soil parameters (OM, total N, pH, P2O5, K2O, Mg, B, WHC, free–living nitrogen fixing and rhizobial microflora properties) and pastures yield were characterized and used to determine relationships in 40 locations covering different growth conditions of the "montado" ecosystem. Soil samples were collected in Spring. Reasonable soil fertility was found. The soils presented, in general, intermediate values for OM, K2O, Mg, and Bo and low values for pH and P2O5. Populations of free-living nitrogen fixing bacteria were high, with an average of 4.2 x 107 CFU g-1 of soil, being nitrogenase activity highly variable, with an average of 34 nmoles of C2H4 g-1 of soil h-1. Rhizobial population associated to Trifolium subterraneum was high, with an average of 106 bacteria g-1 of soil, having adequate nitrogen fixing potential for the majority of the soils. Rhizobial population associated to Medicago polymorpha was low, with an average of 6.5 x 104 bacteria g-1 of soil, an insufficient value for a good nodulation, having low nitrogen fixing potential for the majority of the soils. Annual yield of natural pastures varied highly among locals, with an average of 3245 kg ha-1, a usual value for this ecosystem. In general, soil properties were independent of the soil samples. The chemical parameters OM, P2O5, K2O and total N were important factors to pasture yield. A great variability, even in soil samples collected within a short distance, was observed. A relationship between geological origin and productivity was found, being the granitic soils more productive in non-legume plants
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: Montado ecosystem; pasture yield; soil parameters; sustainable agriculture